(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
An Empirical Mode Decomposition (EMD) method to analyze the similarities of protein sequences is proposed. The EMD method was used to divide a signal sequence converted from a protein sequence into a group of well-behaved Intrinsic Mode Functions (IMFs) and a residue which is monotonic or a trend. This is so that the similarities can be compared among protein sequences by the corresponding residues conveniently and intuitively. This work verifies the method's suitability by using the cytochrome c protein sequences of seven different species.